2013
DOI: 10.1016/j.bmcl.2013.06.048
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of quinoxalines, quinazolines, and 1,5-naphthyridines

Abstract: Several phenyl substituted naphthalenes and isoquinolines have been identified as antibacterial agents that inhibit FtsZ-Zing formation. In the present study we evaluated the antibacterial of several phenyl substituted quinoxalines, quinazolines and 1,5-naphthyridines against methicillin-sensitive and methicillin-resistant Staphylococcus aureus and vancomycin-sensitive and vancomycin-resistant Enterococcus faecalis. Some of the more active compounds against S. aureus were evaluated for their effect on FtsZ pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(60 citation statements)
references
References 37 publications
(24 reference statements)
1
59
0
Order By: Relevance
“…General sensitivity testing on a series of hydrazones, revealed 77 to be the most promising with widest zone of inhibition [90]. Bacteriostatic activity of other quinoxaline derivatives 78 [91], 79 [92], 80 [93], 81 [94] and 82 [95] had been reported. Further studies also established that steroidal-based oxazoloquinoxalines 83 [96a] and its thiazolo-counterpart 84 [96b] were better antibacterial agents than the standard drug amoxicillin and chloramphenicol respectively [96].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…General sensitivity testing on a series of hydrazones, revealed 77 to be the most promising with widest zone of inhibition [90]. Bacteriostatic activity of other quinoxaline derivatives 78 [91], 79 [92], 80 [93], 81 [94] and 82 [95] had been reported. Further studies also established that steroidal-based oxazoloquinoxalines 83 [96a] and its thiazolo-counterpart 84 [96b] were better antibacterial agents than the standard drug amoxicillin and chloramphenicol respectively [96].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Taking this background into account and considering the biologic and antitumor activities of quinazoline derivatives [25][26][27][28][29], the purpose of the present work was to study the cytotoxicity of modified MWCNTs on a human noncancerous cell line (HEK293) and a cancerous one (SKBR3). Our study indicates that MWCNT-quin is highly toxic to cancer cells, and this effect is highly significant compared to its effect on noncancerous cell samples.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Its appeal is further supported for several reasons: (i) it is an essential bacterial protein for survival; (ii) it is highly conserved across many bacterial species, making it a potential broad target; (iii) it is not present in eukaryotes, and toxicity therefore would be expected to be low; and (iv) it is a novel target currently unexploited by other therapeutic options and therefore would be expected to present a low probability of cross-resistance with other therapies. Previous in vitro studies have demonstrated that a number of FtsZ inhibitor compounds contain antibacterial potency against Gram-positive pathogens, including isolates with phenotypic resistance to other antibiotics (14,(45)(46)(47)(48)(49)(50)(51).…”
Section: Figmentioning
confidence: 99%